Representing the atra bilis: The ‘Said’ and ‘Unsaid’ of the Melancholic in Cesare Ripa’s Iconologia - Koźluk, Magdalena (Studia Ceranea, 2024)
This article is the third in a series of works which aims to contribute to documenting the influence of the medical theory of individual temperaments, derived from the theory of the four humors, through the major work Iconologia by the Italian humanist Cesare Ripa (1555–1622). Here, we studied the allegory of the melancholic. Beyond the work aimed at situating it within the medical tradition, we were particularly interested in the relationship between text and image and the interplay between expression (explicite) and silence (implicite) that is so frequent in the work. We thus undertook to analyse all the symbolic attributes of Ripa’s composition according to whether they appear in the engraving, in the text, in both, and whether they are commented on or not. The importance given at the end of the text to the teachings of the School of Salerno also allowed us to better understand the synthetic thought of the Italian humanist and, consequently, the overall economy of the Iconologia. Thus, in the course of our reflection on the modes of expression of the ‘said’ and ‘unsaid’ in the definition of the melancholic temperament in Ripa, we attempted to account for the internal mechanics of his work and the nature of the rhetorical strategies (both textual and visual) of his discursive architecture.